Prognostic Value of MRS Metabolites in Postoperative Irradiated High Grade Gliomas. (3rd August 2015) - Tolia, Maria; Verganelakis, Dimitrios; Tsoukalas, Nikolaos; Kyrgias, George; Papathanasiou, Matilda; Mosa, Eftichia; Kokakis, Ioannis; Kouvaris, John R.; Pissakas, George; Pistevou-Gombaki, Kyriaki; Kelekis, Nikolaos; Kouloulias, Vasileios
Abstract : Purpose . We studied the prognostic significance of Magnetic Resonance Spectroscopy (MRS) in operated high grade gliomas. Materials and Methods . Twelve patients were treated with radiotherapy and Temozolomide. The MRS data were taken four weeks after operation (before radiotherapy) and every six months after the completion of RT. The N-acetyl aspartate, choline, creatine, and myo-inositol parameters were quantified, analyzed, and correlated to recurrence-free survival (RFS). Results . The median RFS was 26.06 months. RFS was significantly worse in elderly patients ( P = 0.001 ) along with the higher choline/creatine ratios at either baseline ( P =   0.003 ) or six months post Radiotherapy ( P = 0.042 ) . Median RFS was 23 months in high choline/creatine levels ≥2 at 6 months after radiotherapy and 11 months for those with <2 choline/creatine levels. There was a significant correlation of maximum difference of choline/creatine ratio with RFS (rho = 0.64, P = 0.045 ). Conclusion . Age and choline/creatine ratio are strong independent prognostic factors in high grade gliomas.